2022
DOI: 10.1021/jacs.1c12106
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Catalytic Reactions for the Stereoselective Synthesis of Cyclic Dinucleotide MK-1454

Abstract: As practitioners of organic chemistry strive to deliver efficient syntheses of the most complex natural products and drug candidates, further innovations in synthetic strategies are required to facilitate their efficient construction. These aspirational breakthroughs often go hand-in-hand with considerable reductions in cost and environmental impact. Enzyme-catalyzed reactions have become an impressive and necessary tool that offers benefits such as increased selectivity and waste limitation. These benefits ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 77 publications
0
33
0
Order By: Relevance
“…We first explored the direct conversion of 3′,5′-protected 2′-ketones 2 to olefin 3 via mild organometallic reagent-mediated olefinations, given the instability of 3 under basic conditions. Although consumption of the starting material was observed in these reactions, to our disappointment, they gave low yields and decomposition, presumably because ketone 2 is hindered and labile (Table ).…”
Section: Resultsmentioning
confidence: 94%
“…We first explored the direct conversion of 3′,5′-protected 2′-ketones 2 to olefin 3 via mild organometallic reagent-mediated olefinations, given the instability of 3 under basic conditions. Although consumption of the starting material was observed in these reactions, to our disappointment, they gave low yields and decomposition, presumably because ketone 2 is hindered and labile (Table ).…”
Section: Resultsmentioning
confidence: 94%
“…Impressive demonstrations of such efforts have recently made headlines in various subfields of chemistry, 58 and we expect nucleoside synthesis to follow these developments soon. Indeed, the recent work of Benkovics et al 59 provides an inspirational example to this end. In their synthesis of the cyclic dinucleotide MK-1454, the combination of organocatalytic fluorination and thiophosphorylation with enzymatic triphosphorylation and cyclization provided the tools for a highly selective synthesis of an enormously challenging target on the process scale.…”
Section: Concluding Remarks "If You Want To Go Fast Go Alone If You W...mentioning
confidence: 99%
“…Previous studies have shown that the CDNs of thiophosphate, rather than parent phosphoric acid CDNs, have higher bioactivity and a stronger activation of STING. MK-1454 is a CDNs of thiophosphate with efficient STING agonistic activity obtained based on P(III) chemical synthesis and structure optimization [ 103 , 104 ]. The phase-II clinical trials of MK-1454 applied to advanced solid tumors or lymphomas have been completed, showing inspiring effects when combined with pembrolizumab (a PD-1 antibody).…”
Section: Sting Inhibitors and Agonistsmentioning
confidence: 99%